Ângulos hiperbólicos e funções hiperbólicas - Rodrigues, Kennedy Félix (2014)
This work has as main objective to study the functions through the concepts and properties of hyperbole. We present a review on trigonometric angles and trigonometric functions in a convenient way for use in the work. A study is made of hyperbole, describing its main elements and properties, such as its equations in canonical form and in the form of equation of the second degree. In the speci c case of the hyperbola of equation xy = a, it is de ned rotation, hyperbolic sector and angle, and properties such as the preservation of a triangle area on hyperbole and hyperbolic sector. A study of the functions hyperbolic, presenting the de nition of sine, cosine and other hyperbolic functions and their properties, like the hyperbolic angle summing relations, which are treated with and without the use of exponential functions.